Analisis Strategi Kompetisi Antara Shopeefood Dan Gofood Dengan Menggunakan Game Theory - Fannia Nur Aziza; Cindy Berliana Latansyah; Revinindia Oktaimanuella (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2023)
ShopeeFood and GoFood are food delivery services that are popular in the community. Both have similar products and services, which is why the competition is getting tougher. To remain competitive, companies must develop optimal strategies to achieve customer satisfaction. The purpose of this research is to determine the right competitive strategy by prioritizing the services offered by companies to customers in choosing food delivery services. The method used in this research is game theory with a descriptive research type. Data analysis techniques used descriptive analysis and SPSS to calculate the validity and reliability of the data. Data is collected through questionnaires distributed to users of the application. From the results of game theory calculations, Shopeefood and GoFood get an optimal game value of 6. The game is solved with a pure ShopeeFood strategy, namely a promotional strategy with a probability of 6. Meanwhile, GoFood also uses a promotional strategy with a probability of 6. In this case, the best strategy is optimal for both services is to improve the promotion strategy.